RELATIONSHIP AMONG PERCEIVED ORGANIZATIONAL SUPPORT AND EMPLOYEE ENGAGEMENT: A STUDY OF UTTRAKHAND - Ms. Sweta Chauhan , Dr. Shilpa Wadhwa (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Employees are considered to be the most important assets of the organization. Employee engagement is considered to be constructive and productive when the organizational support is extensively wider in concept. Perceived organizational support not only improves the employee turnover and absenteeism but it improves the employee engagement and work commitment. The current study is designed to check the relationship of perceived organizational support and employee engagement on academician in education sector. Perceived organizational support relates to employee well being and their contribution is well being acknowledge which improves their employee engagement. The study is aimed to analyze the effect of employees' engagement on higher education academician in Uttrakhand. This study suggested a single hypothesis for this reason. The findings of previous research on the correlation study between “perceived organizational support and employee engagement” have been validated by an evaluation of existing research. This research further illustrates the stronger picture of employee participation that POS is received. Primary data were gathered using a formal questionnaire. There have been 15 questions in the Questionnaire